Momelotinib versus danazol in symptomatic patients with anaemia and myelofibrosis (MOMENTUM): results from an international, double-blind, randomised, controlled, phase 3 study. Issue 10373 (28th January 2023) - Verstovsek, Srdan; Gerds, Aaron T; Vannucchi, Alessandro M; Al-Ali, Haifa Kathrin; Lavie, David; Kuykendall, Andrew T; Grosicki, Sebastian; Iurlo, Alessandra; Goh, Yeow Tee; Lazaroiu, Mihaela C; Egyed, Miklos; Fox, Maria Laura; et al.
Summary: Background: Janus kinase (JAK) inhibitors approved for myelofibrosis provide spleen and symptom improvements but do not meaningfully improve anaemia. Momelotinib, a first-in-class inhibitor of activin A receptor type 1 as well as JAK1 and JAK2, has shown symptom, spleen, and anaemia benefits in myelofibrosis. We aimed to confirm the differentiated clinical benefits of momelotinib versus the active comparator danazol in JAK-inhibitor-exposed, symptomatic patients with anaemia and intermediate-risk or high-risk myelofibrosis. Methods: MOMENTUM is an international, double-blind, randomised, controlled, phase 3 study that enrolled patients at 107 sites across 21 countries worldwide. Eligible patients were 18 years or older with a confirmed diagnosis of primary myelofibrosis or post-polycythaemia vera or post-essential thrombocythaemia myelofibrosis. Patients were randomly assigned (2:1) to receive momelotinib (200 mg orally once per day) plus danazol placebo (ie, the momelotinib group) or danazol (300 mg orally twice per day) plus momelotinib placebo (ie, the danazol group), stratified by total symptom score (TSS; <22 vs ≥22), spleen size (<12 cm vs ≥12 cm), red blood cell or whole blood units transfused in the 8 weeks before randomisation (0 units vs 1–4 units vs ≥5 units), and study site. The primary endpoint was the Myelofibrosis Symptom Assessment Form (MFSAF) TSS response rate at week 24 (defined as ≥50% reduction in mean MFSAF TSS over the 28 days immediately before the end of week 24 compared with baseline). MOMENTUM is registered with ClinicalTrials.gov, number NCT04173494, and is active but not recruiting. Findings: 195 patients were randomly assigned to either the momelotinib group (130 [67%]) or danazol group (65 [33%]) and received study treatment in the 24-week randomised treatment period between April 24, 2020, and Dec 3, 2021. A significantly greater proportion of patients in the momelotinib group reported a 50% or more reduction in TSS than in the danazol group (32 [25%] of 130 vs six [9%] of 65; proportion difference 16% [95% CI 6–26], p=0·0095). The most frequent grade 3 or higher treatment-emergent adverse events with momelotinib and danazol were haematological abnormalities by laboratory values: anaemia (79 [61%] of 130 vs 49 [75%] of 65) and thrombocytopenia (36 [28%] vs 17 [26%]). The most frequent non-haematological grade 3 or higher treatment-emergent adverse events with momelotinib and danazol were acute kidney injury (four [3%] of 130 vs six [9%] of 65) and pneumonia (three [2%] vs six [9%]). Interpretation: Treatment with momelotinib, compared with danazol, resulted in clinically significant improvements in myelofibrosis-associated symptoms, anaemia measures, and spleen response, with favourable safety. These findings support the future use of momelotinib as an effective treatment in patients with myelofibrosis, especially in those with anaemia. Funding: Sierra Oncology.